System integration for real-time laser scanning confocal microscope - Gumus, G.; Sarioglu, B.; Gokdel, Y.D. (Institute of Electrical and Electronics Engineers Inc., 2016)
In this work, a laser scanning confocal microscopy system governed by a software controlled DAQ Card is presented. The presented system can be utilized for scanning a target and displaying the resulting image through a designed graphical user interface (GUI). The system performs two main operations: (1) generation of the actuation signal and (2) image acquisition. The architecture of the proposed system and successful operation of the system is demonstrated by constructing images from USAF51 negative resolution test target. In the experiments, the proposed system is operated at the slow scan frequency (fslow) of 1 Hz and the fast scan frequency (ffast) of 100 Hz with a sampling frequency (fs) of 20 kHz. The experimental results show that 1 ?m lateral resolution is achieved in the proposed system. © 2016 IEEE.
Gerçek Zamanli Lazer Taramali Konfokal Mikroskop için Sistem Entegrasyonu
24th Signal Processing and Communication Application Conference, SIU 2016 -- 16 May 2016 through 19 May 2016 -- -- 122605
Keywords: Confocal Microscope; İmage Processing; Laser Scanning Microscope; Confocal Microscopy; Graphical User İnterfaces; Image Acquisition; Image Processing; Laser Applications; Microscopes; Scanning; Surface Analysis; User İnterfaces; Graphical User İnterfaces (Guı); Laser Scanning Confocal Microscopes; Laser Scanning Confocal Microscopy; Laser Scanning Microscope; Lateral Resolution; Resolution Test-Target; Sampling Frequencies; System İntegration; Signal Processing